Hindu Priests at Temple, Trinidad - (:unkn) unknown (Printed in U.S.A., 2008)
Here is a photo of three East Indian holy men - a pundit at middle flanked by holy men playing Indian musical instruments. They are standing in front of a Hindu temple which has an image of the Hindu deity, Lord Hanuman, on the wall at left.
Colour: Black and White; Style: Landscape; Other: Bordered, Divided
Keywords: Postcards; Hindu priests--Trinidad and Tobago; Hindu temples--Trinidad and Tobago; Trinidad and Tobago; Hinduism--Prayers and devotions; Hindu gods--Trinidad and Tobago; Musical instruments--India; Architecture--Trinidad and Tobago; Plants--Trinidad and Tobago; Hindu decoration and ornament--Trinidad and Tobago